Monstros no Cordel: uma análise semiótica da monstruosidade na poesia popular nordestina - Rodrigues, Felipe Lima (2025)
This thesis aims to analyze the presence of monsters in Cordel Literature pamphlets, based on specific works selected from specific collections. It aims to investigate the phenomenon of monstrosity in popular poetry from the perspective of Cultural Semiotics, particularly the Tartu-Moscow School, as exemplified by Russian semiotician Yuri Lotman. The analyses adopted Lotman’s semiotic structural method as a tool for developing models of highly complex systems—among them, cultural texts—whose dynamic nature, transforming over time and space, requires observation and analysis of their semiotic processes in their variations. Based on this triad—the monstrous body, the semiotic frontier through which it transits, and its persistence over time—the thesis seeks to understand the phenomenon of monstrosity in Cordel Literature, relating it to the concepts of semiosphere, border, modeling, memory, and forgetting, as proposed by Cultural Semiotics. The paper observes that the monstrous presence in the pamphlets of Cordel Literature constitutes vestiges of ancestral rites: mundane reproductions of myths now desecrated, but permeated by the Christian beliefs of the backlands and the worldviews of the cordel poets. Charged with symbolic power and in an eternal search for translation, the monster continues to roam the semiotic frontiers of the backlands, attracting and repelling the gaze of travelers, pilgrims, and singers, readers and spectators of the performance.